Corticosteroid treatment in Sydenham's chorea. (March 2018) - Fusco, C.; Spagnoli, C.
Abstract: Sydenham's chorea (SC) is an immune-mediated hyperkinetic movement disorder, developing after group A Beta-hemolytic streptococcal (GABHS) infection. Aside from conventional symptomatic treatment (carbamazepine, valproate, neuroleptics), the use of steroids has also been advocated, mainly in severe, drug-resistant cases or if clinically disabling side effects develop with first line therapies. Based on the description of 5 cases followed in the Child Neurology Unit of Santa Maria Nuova Hospital in Reggio Emilia and on the available medical literature on this topic, we propose considering the use of corticosteroids therapy in children with SC, with the administration of IV methyl-prednisolone followed by oral deflazacort in severe cases and of oral deflazacort alone in mild and moderate degrees of involvement. In our experience this therapy is effective both in the short and long-term period, in different clinical presentations (chorea paralytica, distal chorea, hemichorea, "classic" chorea, association with mood disorder or dyspraxia) and very well tolerated (no significant side effects were recorded). Highlights: Sydenham's chorea (SC) is a dysimmune hyperkinetic movement disorder. No evidence-based treatment is available. In severe/refractory cases immune suppression with steroids has been used. We report our experience with clinically heterogeneous, mild-to-severe SC. We found good short and long-term efficacy and tolerability with corticosteroids.